2016
DOI: 10.1080/0092623x.2016.1147511
|View full text |Cite
|
Sign up to set email alerts
|

Shame, Catastrophizing, and Negative Partner Responses Are Associated With Lower Sexual and Relationship Satisfaction and More Negative Affect in Men With Peyronie's Disease

Abstract: Peyronie's disease (PD) has a negative impact on men's sexual functioning and quality of life, but little is known about why some men cope better than others and what the effects of PD are on their relationships. The aims of the present study were to describe negative affect, pain, and relationship and sexual satisfaction in men with PD, and to explore their psychosocial correlates. Participants were 110 men diagnosed with PD. All men completed questionnaires. The main outcome measures were as follows: Global … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…The combination of negative emotions and reduced frequency of sex may substantially impact the emotional and sexual health of patients and their partners. For example, relationship difficulties in men with PD have been reported frequently [11, 12, 16], and in the current study, one-fifth of patients said that PD negatively impacted their relationships with their partners. Although the factors underlying these relationship difficulties are likely diverse, emotional difficulties and the ability to have intercourse both have been shown to predict relationship problems [11].…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…The combination of negative emotions and reduced frequency of sex may substantially impact the emotional and sexual health of patients and their partners. For example, relationship difficulties in men with PD have been reported frequently [11, 12, 16], and in the current study, one-fifth of patients said that PD negatively impacted their relationships with their partners. Although the factors underlying these relationship difficulties are likely diverse, emotional difficulties and the ability to have intercourse both have been shown to predict relationship problems [11].…”
Section: Discussionmentioning
confidence: 52%
“…Although the factors underlying these relationship difficulties are likely diverse, emotional difficulties and the ability to have intercourse both have been shown to predict relationship problems [11]. Furthermore, catastrophizing, increased bother or distress and reduced sexual frequency have been reported to negatively impact sexual satisfaction in men with sexual difficulties [16–18]. However, female partners of men with sexual dysfunction may not be as impacted by these symptoms as was once thought.…”
Section: Discussionmentioning
confidence: 99%
“…Penile curvature and pain during erection present a significant bothersome issue for both men with PD and their partner [6][7][8].…”
Section: Discussionmentioning
confidence: 99%
“…12 Preliminary research has also shown negative partner reactions to be associated with lower sexual and relationship satisfaction in men with PD. 13 Assessment of the emotional, psychosexual, and relationship aspects of the patient’s PD symptoms that negatively impact the patient’s quality of life, are needed to prioritize treatment goals. 14…”
Section: Introductionmentioning
confidence: 99%